Acceptability of routine HIV counselling and testing, and HIV seroprevalence in Ugandan hospitals - Wanyenze, Rhoda K.; Nawavvu, Cecilia; Namale, Alice S.; Mayanja, Bernard; Bunnell, Rebecca; Abang, Betty; Amanyire, Gideon; Kamyaa, Moses R.; Sewankambo, Nelson K. S. (World Health Organization, 2008)
Mulago and Mbarara hospitals are large tertiary hospitals in Uganda with a high HIV/AIDS burden. Until recently, HIV testing was available only upon request and payment. From November 2004, routine free HIV testing and counselling has been offered to improve testing coverage and the clinical management of patients. All patients in participating units who had not previously tested HIV-positive were offered HIV testing. Family members of patients seen at the hospitals were also offered testing. Methods Data collected at the 25 participating wards and clinics between 1 November 2004 and 28 February 2006 were analysed to determine the uptake rate of testing and the HIV seroprevalence among patients and their family members. Findings Of the 51 642 patients offered HIV testing, 50 649 (98%) accepted. In those who had not previously tested HIV-positive, the overall HIV prevalence was 25%, with 81% being tested for the first time. The highest prevalence was found in medical inpatients (35%) and the lowest, in surgical inpatients (12%). The prevalence of HIV was 28% in the 39 037 patients who had never been tested before and 9% in those who had previously tested negative. Of the 10 439 family members offered testing, 9720 (93%) accepted. The prevalence in family members was 20%. Among 1213 couples tested, 224 (19%) had a discordant HIV status. Conclusion In two large Ugandan hospitals, routine HIV testing and counselling was highly acceptable and identified many previously undiagnosed HIV infections and HIV-discordant partnerships among patients and their family members.
Keywords: HIV; Counselling; Seroprevalence; Hospitals